2022
DOI: 10.1186/s12885-022-09516-1
|View full text |Cite
|
Sign up to set email alerts
|

Activated TAZ induces liver cancer in collaboration with EGFR/HER2 signaling pathways

Abstract: Background Liver cancer is a major global health concern due to the steady increases in its incidence and mortality. Transcription factors, yes-associated protein (YAP) and WW domain-containing transcription regulator protein 1 (WWTR1, also known as TAZ) have emerged as critical regulators in human hepatocellular carcinoma (HCC) and cholangiocarcinoma (CC), the two major types of primary liver cancer. However, our study as well as other previous reports have shown that activation of YAP and TAZ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…The results showed that the nuclear to total ratio of YAP/TAZ was not significantly affected by the surface roughness, but total YAP/TAZ levels were significantly altered for both cells ( Figures 6D–H ). This finding is in agreement with previous studies demonstrating an interplay between EGFR and YAP/TAZ in several cancers including TNBC, and their effect in tumorigenic properties ( Cancer Discov, 2020 ; Ando et al, 2021 ; Moon et al, 2022 ; Soyama et al, 2022 ; Zhang and Li, 2022 ). Overall, this data confirms a mechanosensing effect in a roughness-dependent manner and suggests that changes in the EGF/EGFR signaling pathway are a result of altered YAP/TAZ levels driven by changes in surface roughness.…”
Section: Resultssupporting
confidence: 93%
“…The results showed that the nuclear to total ratio of YAP/TAZ was not significantly affected by the surface roughness, but total YAP/TAZ levels were significantly altered for both cells ( Figures 6D–H ). This finding is in agreement with previous studies demonstrating an interplay between EGFR and YAP/TAZ in several cancers including TNBC, and their effect in tumorigenic properties ( Cancer Discov, 2020 ; Ando et al, 2021 ; Moon et al, 2022 ; Soyama et al, 2022 ; Zhang and Li, 2022 ). Overall, this data confirms a mechanosensing effect in a roughness-dependent manner and suggests that changes in the EGF/EGFR signaling pathway are a result of altered YAP/TAZ levels driven by changes in surface roughness.…”
Section: Resultssupporting
confidence: 93%
“…TAZ upregulation in NASH and HCC has been associated with both increased cholesterol levels and decreased AMPKα activity and it has been described to participate in the transcriptional regulation of several genes involved in fibrosis, proliferation, superoxide formation and regulation of metabolism. Its upregulation has been described in pre-tumor NASH stage (50, 67, 71). In accordance with these studies, we also found a marked upregulation of TAZ levels in NASH livers that was partially abrogated in mice lacking miR-33 in hepatocytes (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…10E). Recent studies have highlighted the role of the gene regulator TAZ in NASH worsening and progression to HCC (46,47,50,67,68). YAP/TAZ are transcriptional coactivators of the Hippo pathway that participate in the initiation and progression of different cancers (68)(69)(70).…”
Section: Mir-33 Deficiency In Hepatocytes Reduces Nafld Progression T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Once it moves out to the cytoplasm and is phosphorylated, its activity is suppressed. The Hippo signaling pathway manages its activity and when the pathway is inhibited, YAP continuously remains in the nucleus and shows oncogenic activity [ [13] , [14] , [15] , [16] , [17] ].…”
Section: Introductionmentioning
confidence: 99%